Reconnaissance analysis on buildings damaged during Durres earthquake Mw6.4, 26 November 2019, Albania: effects to non-structural elements - Sheshov, V.; Apostolska, R.; Bozinovski, Z.; Vitanova, M.; Stojanoski, B.; Edip, K.; Bogdanovic, A.; Salic, R.; Jekic, G.; Zafirov, T.; Zlateski, A.; Chapragoski, G.; et al. (Springer Science and Business Media LLC, 2021)
At 03:56 local time on November 26, 2019, an earthquake with a Mw = 6.4 struck western part of Albania. The duration of the tremor lasted less than 50 s and was felt largely also in Albania's capital Tirana, and in places as far away more than 300 km northeast of the epicenter. It caused damage to many public and residential buildings in districts of Durres, Tirana, Lezha, Shkodra, Diver, Berat and surrounding areas. This paper describes rapid visual assessment of the damaged buildings (169 in total) in affected areas by IZIIS teams’ inspection of damaged buildings. Severe damages were identified in structural and non-structural elements as a result of inconsistent application of recent knowledge in design, construction and quality control of earthquake resistant structures. Structural errors in design and construction as well as inappropriate quality of built-in materials have been observed. Such results from the rapid damage assessment leads to the necessity of taking specific measures as detailed engineering inspection of vital structures as a basis of definition corresponding technical solutions for repair and strengthening with aim of restoring their operational mode. Last but not least, the biggest effect of earthquake damage was observed in non-structural elements which made the structures not-usable for citizens of the earthquake region.